2014
DOI: 10.1186/1471-2407-14-294
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EGFR mutations in plasma and biopsies from non-small cell lung cancer patients by allele-specific PCR assays

Abstract: BackgroundLung cancer patients with mutations in the epidermal growth factor receptor (EGFR) are primary candidates for EGFR-targeted therapy. Reliable analyses of such mutations have previously been possible only in tumour tissue. Here, we demonstrate that mutations can be detected in plasma samples with allele-specific PCR assays.MethodsPairs of the diagnostic biopsy and plasma obtained just prior to start of erlotinib treatment were collected from 199 patients with adenocarcinoma of non-small-cell lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 13 publications
6
100
0
2
Order By: Relevance
“…A total of 2 mL of blood was used for cfDNA extraction using the cobas cell-free DNA Purification Kit (in development; ref. 22). The cfDNA was eluted in 100 mL, 75 mL…”
Section: Biomarker Analysismentioning
confidence: 99%
“…A total of 2 mL of blood was used for cfDNA extraction using the cobas cell-free DNA Purification Kit (in development; ref. 22). The cfDNA was eluted in 100 mL, 75 mL…”
Section: Biomarker Analysismentioning
confidence: 99%
“…ctDNA can be used to identify resistance to TKIs [126][127][128][129][130][131][132][133][134][135]. Weber et al [136] demonstrated a concordance rate of 90% (179/199) for EGFR mutations between biopsy tissue and ctDNA (plasma) before EGFR TKIs. These authors identified EGFR mutations in the plasma not identified in the biopsy, probably related to sampling issues or heterogeneity [136].…”
Section: Doi: 101159/000487440mentioning
confidence: 99%
“…By contrast, tumor regression correlates to decreased ctDNA burden in cfDNA. With regard to specific genetic alterations, one clear example is the clinical utility of the detection of EGFR mutations in the cfDNA of NSCLC patients treated with gefitinib (25) or erlotinib (26). EGFR mutations have also been shown to be of prognostic and predictive value, and patients with an activating mutation in EGFR in cfDNA have been reported to respond significantly better to TKIs (27).…”
Section: Circulating Free Dna (Cfdna) As Prognostic and Monitoring Tementioning
confidence: 99%